Initial-Stage Primary Intraosseous Squamous Cell Carcinoma Derived from Odontogenic Keratocyst with Unusual Keratoameloblastomatous Change of the Maxilla: A Case Report and Literature Discussion - Kentaro Kikuchi; Fumio Ide; Shota Takizawa; Seiji Suzuki; Hideaki Sakashita; Tie-Jun Li; Kaoru Kusama (Case Reports in Otolaryngology)
Primary intraosseous squamous cell carcinoma (PIOSCC) is a rare malignant neoplasm derived from odontogenic epithelial remnants in the central jaw bone. Most PIOSCCs originate from odontogenic cysts with a nonkeratinized epithelial lining, especially from radicular/residual and dentigerous cysts. There have been few reports of PIOSCCs derived from the odontogenic keratocyst (OKC), particularly those describing pathological features at the initial stage. The diagnosis of PIOSCC is difficult and based on exclusion of other carcinomas, including metastatic tumors from other primary sites. Here, we report an extremely rare case of initial-stage PIOSCC derived from the OKC with unusual keratoameloblastomatous change of the maxilla.